Optimalisasi Media Sosial untuk Mengatasi Masalah Pemasaran Djajan Coffee: Penelitian - Devy Any Ghotri; Tirsha Nurcitra Virginia; Muhammad Yunus Hatori Candra; Deni Saeful Rizal; Nana Supriana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Marketing problems are one of the major challenges faced by UMKM Djajan Coffee, especially amid increasing business competition and shifting consumer behavior that relies heavily on social media for product information. This community engagement activity aims to optimize the use of social media as a promotional tool to enhance business visibility and attract more customers. The implementation method includes observation, interviews, marketing needs analysis, and direct mentoring for the business owner regarding digital promotion strategies. The programs carried out consist of creating visual content, preparing a posting schedule, utilizing Instagram and TikTok promotional features, and providing basic training on online brand management. The results indicate an improvement in the owner’s capability to manage social media, higher customer engagement through more consistent content, and a significant increase in account reach. The optimization of social media not only improves Djajan Coffee’s marketing effectiveness but also strengthens its brand identity and competitiveness in the local market. This activity demonstrates that a well-planned digital marketing strategy can serve as an effective solution to overcome marketing issues faced by UMKM.